2018
DOI: 10.1007/s00223-018-0461-x
|View full text |Cite
|
Sign up to set email alerts
|

Early Fracture Healing is Delayed in the Col1a2+/G610C Osteogenesis Imperfecta Murine Model

Abstract: Osteogenesis imperfecta (OI) is a rare heritable skeletal dysplasia mainly caused by type I collagen abnormalities and characterized by bone fragility and susceptibility to fracture. Over 85% of the patients carry dominant mutations in the genes encoding for the collagen type I α1 and α2 chains. Failure of bone union and/or presence of hyperplastic callus formation after fracture were described in OI patients. Here we used the Col1a2 mouse, carrying in heterozygosis the α2(I)-G610C substitution, to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…Even when OI patient fractures do successfully heal, refractures typically go unreported and fracture databases do not distinguish between contralateral limbs, resulting in little to no information concerning the strength of OI bone after healing . Two recent studies showed delayed fracture healing in OI mouse models . These studies, however, did not explore the biomechanical consequences of abnormal fracture healing in OI murine models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even when OI patient fractures do successfully heal, refractures typically go unreported and fracture databases do not distinguish between contralateral limbs, resulting in little to no information concerning the strength of OI bone after healing . Two recent studies showed delayed fracture healing in OI mouse models . These studies, however, did not explore the biomechanical consequences of abnormal fracture healing in OI murine models.…”
Section: Introductionmentioning
confidence: 99%
“…(13) Two recent studies showed delayed fracture healing in OI mouse models. (28,29) These studies, however, did not explore the biomechanical consequences of abnormal fracture healing in OI murine models. Thus, there is an unmet need to better understand the mechanisms by which OI affects fracture healing and its relation to healed bone quality and strength in the context of abnormal matrix and signaling.…”
Section: Introductionmentioning
confidence: 99%
“…While these patients are more prone to fracture than the general population, fracture healing is also affected by the inherent poor bone quality and can be complicated by non-union and refracture (66,67). Studies in dominant and recessive mouse models of OI show delayed fracture healing and reduced strength of the healed bone (68,69). While fractures, particularly in young children, may be treated nonoperatively with immobilization, this can result in muscle weakness, joint stiffness and disuse osteopenia.…”
Section: Fracturesmentioning
confidence: 99%
“…These characteristics make the Col1a2 G610C/+ (G610C) model attractive for intervention studies and biomechanical analysis. Accordingly, the model has been used to investigate the role of mutant collagen in causing OI symptoms such as growth deficiencies [11], defective mineralization of developing bone [12], disrupted osteoblast differentiation [13], and impaired fracture healing [14]. It has also been used in preclinical trials of OI treatments such as upregulating the LRP5 pathway [15,16], diet-based attempts to degrade mutant procollagen and thereby increase bone strength [17,18], sclerostin antibody and zoledronate combination therapy [19], bone marrow transplant [20], TGF-beta inhibition [16,21], activin receptor inhibitor treatment to improve muscle contractility [22], myostatin inhibition [23], and BMP-2 injections for fracture healing [24].…”
Section: Introductionmentioning
confidence: 99%